An account of the manor of Kilmoon, and the copyhold tenure existing there - O'Brien, Murrough (Statistical and Social Inquiry Society of Ireland, 1879)
It is generally supposed that there are no copyhold lands in Ireland, though at one time they were not altogether unknown. The only mention of their existence in modern times, that I have found, is in Vance and Ferguson's Tenure and Prosperity of Ireland, which says: ?The copyhold tenure so prevalent in England has not been known to exist in Ireland, unless in some exceptional cases, such as the manor of Kilmoon, or Primatestown, in the County of Meath, where it is said to be found?. It is, I believe, certain that these are now the only copyhold lands in Ireland, and as this tenure will cease to exist in Ireland by the sale, under the Irish Church Act, of the lands in the manor of Kilmoon, some account of the manor may be of interest to the Statistical Society.
Read before the Society, 21 May 1878
Keywords: Land ownership in 19th century Ireland; Copyhold tenure; Kilmoon Manor; 314.15